2019
DOI: 10.5539/gjhs.v11n10p134
|View full text |Cite
|
Sign up to set email alerts
|

Proximity and Density of Alcohol Outlets as a Risk Factor of Alcohol Abuse Amongst the Youth: A Case Study of a Border Town in Northern Region of Namibia

Abstract: The proximity and density of alcohol outlets are positively associated with drinking patterns and increase in alcohol consumption resulting in deviant behaviors such as excessive drinking, risky sexual behaviors, violent and crime in communities. This study was aimed at identifying and assessing the proximity, density of alcohol outlets as a risk factor to potential behavioral influence amongst the youth in a border town in the northern region of Namibia. The study was qualitative in nature and used ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The researchers are aware that human body requires alcohol (Paton 2005), as such, they are not arguing that fact, but they speak of abuse of alcohol that militate against the quality of life in migrant youth. Evidently, there are numerous alcohol outlets that are mushrooming in rural communities globally and South Africa is not an exception (Hasheela et al 2019;Hasheela, Ananias and Schenek 2020). In light of that, participants in this study shared the sentiments that there is accessibility and availability of alcohol in their place of residence as migrants.…”
Section: Accessibility and Availability Of Alcoholmentioning
confidence: 73%
See 1 more Smart Citation
“…The researchers are aware that human body requires alcohol (Paton 2005), as such, they are not arguing that fact, but they speak of abuse of alcohol that militate against the quality of life in migrant youth. Evidently, there are numerous alcohol outlets that are mushrooming in rural communities globally and South Africa is not an exception (Hasheela et al 2019;Hasheela, Ananias and Schenek 2020). In light of that, participants in this study shared the sentiments that there is accessibility and availability of alcohol in their place of residence as migrants.…”
Section: Accessibility and Availability Of Alcoholmentioning
confidence: 73%
“…In essence, migrants' youth challenge of binge consumption should be viewed in conjunction to the environment they find themselves at. In that note, binge drinking could be as a result of high density of alcohol outlets in the community (Hasheela, Makhubele, Ananias, Matlakala, Mafa, Chiwalo, Rapholo, Freeman, Svinurai, and Hamuse 2019). On that score, an intervention to an individual and returning them to an environment with abundance of alcohol is a recipe to relapse.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These findings confirm ease of alcohol access by learners both around schools and in the communities, consistent with studies conducted in South Africa [ 21 , 24 , 31 ] and other countries [ 39 , 59 , 60 ]. Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia. Studies have reported that the more alcohol outlets within school vicinity and in the communities, the more likely youths will engage in drinking alcohol, and this has been reported in countries such as South Africa [ 21 , 24 , 31 ], Namibia [ 39 ], Brazil [ 59 ] and Canada [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjective or psychological availability refers to the perception of accessible people on alcohol and their response to alcohol marketing [ 26 ]. Researchers in other countries, including South Africa, have reported an established positive link between the number of liquor outlets found in a locality, as well as proximity, density of alcohol outlets and indulgence in alcohol use in the communities [ 24 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation